2015
DOI: 10.1007/s11128-015-1062-5
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement of magnetic impurities through electron scattering in an electric field

Abstract: We show that the entanglement between two distant magnetic impurities, generated via electron scattering, can be easily modulated by controlling the magnitude of an applied external electric field. We assume that the two magnetic impurities are fixed and located on an one-dimensional quantum wire. A ballistic electron moving through the wire is scattered off by both

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…An ideal filter would have I (1) = 1, and B = B 0 α 0 . We have shown that the equations of motion for the ORCA buffer allow for unit memory efficiencies, with K = 1 [22], which with proper mode matching can optimally filter QD emission. To improve the predicted performance closer to an ideal quantum buffer additional numerical optimizations are required, for example adjusting the interaction length and temperature, (2) (a.u.)…”
Section: Fig 3: Simulation Of Comparison Of Purification Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal filter would have I (1) = 1, and B = B 0 α 0 . We have shown that the equations of motion for the ORCA buffer allow for unit memory efficiencies, with K = 1 [22], which with proper mode matching can optimally filter QD emission. To improve the predicted performance closer to an ideal quantum buffer additional numerical optimizations are required, for example adjusting the interaction length and temperature, (2) (a.u.)…”
Section: Fig 3: Simulation Of Comparison Of Purification Effectmentioning
confidence: 99%
“…The brightness will then be: B out = B 0 α 0 |λ 0 | 2 , where B 0 is the brightness of the photon source prior to our quantum buffer and α 0 is the fraction of the dominant mode of the source emission. For our ORCA buffer, the device becomes multimode due to the choices of several parameters, such as the length of the atomic medium, the detuning, the control field the temporal shape and its energy [22]. The output of an ORCA buffer is a mixture of different modes described by the density matrix…”
mentioning
confidence: 99%